Information Security Policies and Procedures: A Practitioner's Reference, Second Edition - R. Peltier, Thomas (CRC Press, 2009)
Policies, standards, and procedures are a key element in the business process. The implementation of these documents should never be undertaken to satisfy some perceived audit or security requirement. These requirements do not exist. There are only business objectives or mission requirements. This book is dedicated to the concept that policies, standards, and procedures support the efficient running of an organization. Standards and procedures are the elements that implement the management policies.